La Cour suprême, la fiducie d'investissement et le prospectus - Demers, Robert (Les Cahiers de droit, 1978)
The possibility of establishing investment trusts in the Province of Québec was examined recently by the Supreme Court in the Higher case. Investment trusts, in Québec, are possibly created as a species of contract but as civil law trusts, they cannot be admitted. This point is well settled by the case. The court also examines the recourse in damages under article 1065 C.C. for inexecution of promises contained in a prospectus: the provincial courts were well familiar with recourses in delict in such cases but contractual relief, although suggested, was not clearly admitted. The case now offers a definite answer to this uncertainty.